Burnout as a central mechanism linking job demands and employee performance: A bibliometric review - Rahmawati, Siti Sucia; Suwatno, Suwatno; Rofaida, Rofi (Indonesian Research Journal in Education |IRJE|, 2026)
This study aims to examine how burnout is positioned as a central mechanism linking job demands and employee performance through a bibliometric review of recent literature. Data were retrieved from the Scopus database, covering peer-reviewed journal articles published between 2021 and 2025. A total of 31 articles were analyzed using bibliometric techniques, including publication trend analysis, authorship and geographical distribution, and keyword co-occurrence mapping with VOSviewer. The analysis suggests that burnout is repeatedly discussed as a key link between different forms of job demands and employee performance outcomes across the reviewed studies. However, employee performance is less explicitly integrated than job demands and burnout, indicating a fragmented research landscape. These findings indicate that future studies may benefit from adopting more comprehensive frameworks that explain how burnout connects job demands with performance. The study provides a systematic foundation for future empirical research and organizational interventions.